The builds and functional relations Between the peopolitics and strategy - المدرس الدكتورة مھا ذیاب حمید (College of Education for Women, 2019)
The geopolities considering as build from the basies builds of the polities geography, participating in appointing the military geography, and submit to it geo-polities purveyed, playing important role to appointing the builds relations between the high strategy and the military strategy, while the foreign polities of the state, which considering as a tool for the state outside it environment and borders playing the role of the performance and the functional works to the peaceful or hostile reaction according to the geopolities purveyed which participating in amassing the recourse for the economical, political, social, military and technology strategies and activating it to achieving the state interests and objects.